Study on the Failure Mechanism of Strain Rockburst - Lichao Zhou; Gang Wang; Rong Hu; Xiqi Liu; Dongxing Wang; Leibo Song; Yong Niu (Shock and Vibration)
Among the factors affecting rock mass failure, the stress state has the greatest influence on the mechanical behavior of rock. The mechanical behavior of rock depends on the change of stress path, and the stress of rock mass is closely related to deformation and failure. In order to study the influence of surrounding rock stress state on the failure mode of surrounding rock, based on the theory of elastic mechanics and fracture mechanics, this paper analyzed the stress state of surrounding rock element and crack propagation of surrounding rock, and estimated the potential failure mode of surrounding rock in different areas of a phosphate mine in Yichang. The results showed that: the surrounding rock element is affected by the gradient stress, and a larger stress gradient corresponds to a larger principal stress ratio and variation direction of the surrounding rock. The failure mode of surrounding rock is affected by the coupling effect of principal stress ratio and principal stress direction. Under the action of certain crack angle and appropriate confining pressure, different fracture mechanisms may occur in the surrounding rock compression. But the partition of surrounding rock failure mode region can predict the surrounding rock failure mode to a certain extent.